A Biomimetic Drosera Capensis with Adaptive Decision‐Predation Behavior Based on Multifunctional Sensing and Fast Actuating Capability (Adv. Funct. Mater. 13/2022). (23rd March 2022) - Qiu, Ye; Wang, Chengjun; Lu, Xiaoyan; Wu, Huaping; Ma, Xiaolong; Hu, Jiahui; Qi, Hangcheng; Tian, Ye; Zhang, Zheng; Bao, Guanjun; Chai, Hao; Song, Jizhou; et al.
Abstract : Adaptive Actuation In article number 2110296, Huaping Wu, Jizhou Song, Aiping Liu, and co‐workers develop a biomimetic Drosera capensis that is capable of multifunctional self‐sensing, automatic regulation, and adaptive actuation to diverse stimuli in a closed‐loop fashion. With the synergistic effect of multifunctional sensing and fast actuating schemes, the artificial drosera capensis deconvolutes multiple catching features and thus holds impressive predatory behavior for ideal‐sized prey.